Epidemiological aspects of melanoma at a university hospital dermatology center over a period of 20 years Aspectos epidemiológicos do melanoma em serviço de dermatologia de hospital universitário em um período de 20 anos - Flavia Vieira Brandão; Ana Francisca Junqueira Ribeiro Pereira; Bernardo Gontijo; Flávia Vasques Bittencourt (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: The incidence of melanoma has been steadily rising in past decades. Although it accounts for only 3% of all skin cancers, it is responsible for 75% of deaths. OBJECTIVE: to describe the epidemiological aspects of melanoma in a university hospital setting over a period of 20 years. METHODS: A total of 166 patients were analyzed between January 1990 and January 2010 for clinical and histological variables and correlations between them. A 5% level of significance was adopted. RESULTS: The majority of patients were Caucasians (74%), females (61%), with a mean age at diagnosis of 55. The predominant histological type was lentigo maligna/lentigo maligna melanoma (35.7%) and the head and neck was the most affected site (30.7%). Among non-Caucasians, the acral region was the most affected. Most tumors were in situ (41.1%). Growth of the lesion was the most frequent complaint (58.1%) and bleeding was most frequently associated with melanomas with a depth > 4mm. There were seven deaths (4.2%), with a high risk among men, non-Caucasians and those under 20 years of age, with a Breslow's depth > 2mm, with lentiginous acral melanoma and with a history of growth and bleeding. CONCLUSIONS: Our sample differs from most of the studies in the predominant location (head and neck), histological type (lentigo maligna/ lentigo maligna melanoma) and a major risk of death under the age of 20, which could be with a reflex of regional variation. Broader studies are necessary for validation of the results. FUNDAMENTOS: A incidência do melanoma cutâneo aumentou nas últimas décadas. Embora represente 3% dos tumores cutâneos, é responsável por 75% dos óbitos. O diagnóstico precoce constitui a principal chance de cura. OBJETIVO: Descrever os aspectos epidemiológicos do melanoma em hospital universitário em 20 anos. MÉTODOS: Avaliaram-se 166 pacientes no período de janeiro de 1990 a janeiro de 2010, quanto s variáveis epidemiológicas, histológicas e óbitos relacionados ao melanoma e suas correlações. Adotou-se nível de significância de 5%. RESULTADOS: A maioria dos pacientes era brancos (74%), mulheres (61%), com média de idade ao diagnóstico de 55 anos. O tipo histológico predominante foi o lentigo maligno/lentigo maligno melanoma (35,7%) e a localização mais frequente foi a cabeça e o pescoço (30,7%). Entre os não-brancos, a região acral foi a mais acometida. Quanto espessura tumoral, a maioria dos melanomas era in situ (41,1%). O crescimento da lesão foi a queixa mais frequente (58%) e o sangramento foi mais associado a melanomas espessos. Ocorreram sete óbitos (4,2%), com maior risco de morte em menores de 20 anos e naqueles com história de sangramento, após análise multivariada. CONCLUSÃO: Esta casuística difere da maioria dos estudos em relação localização (cabeça e pescoço), ao tipo histológico (lentigo maligno/lentigo maligno melanoma) e ao maior risco de óbito em menores de 20 anos, o que pode ser devido variação regional. Estudos mais amplos são necessários para validação destes resultados.